Hubungan Teknik Jahitan terhadap Gejala Infeksi Luka Perineum pada Ibu Nifas Hari Keenam di BPM Sri Utami Surabaya - Andarwulan, Setiana (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2020)
Perineal injury occurs almost every first labor and is not uncommon. Perineal injuries occur due to excessive head extension, the majority of which occur during rotation. Normal childbirth care recommends using the most efficient suture technique for the wound in suturing. Bold stitches have the advantage of being able to close the wound more tightly. This s